METH-Induced Neurotoxicity Is Alleviated by Lactulose Pretreatment Through Suppressing Oxidative Stress and Neuroinflammation in Rat Striatum - Xie, Xiao-Li; Zhou, Wen-Tao; Zhang, Kai-Kai; Chen, Li-Jian; Wang, Qi (Frontiers in Neuroscience, 2018)
Abuse of methamphetamine (METH) results in neurological and psychiatric abnormalities. Lactulose is a poorly absorbed derivative of lactose and can effectively alleviate METH-induced neurotoxicity in rats. The present study was designed to investigate the effects of lactulose on METH-induced neurotoxicity. Rats received METH (15 mg/kg, 8 intraperitoneal injections, 12-hour interval) or saline and received lactulose (5.3 g/kg, oral gavage, 12-hour interval) or vehicle 2 days prior to the METH administration. Reactive oxygen species (ROS) and malondialdehyde (MDA) were measured. Protein levels of toll-like receptor 4 (TLR4), myeloid differentiation factor 88 (MyD88), tumor necrosis factor receptor associated factor 6 (TRAF6), nuclear factor κB (NFκB), interleukin (IL)-1β, IL-6, TNF-α, cleaved caspase 3 and poly(ADP-ribose) polymerase-1 (PARP-1) were determined by western blotting. mRNA expressions of nuclear factor erythroid 2-relatted factor-2 (Nrf2), p62 and heme oxygenase-1 (HO-1) were assessed by RT-qPCR. The lactulose pretreatment decreased METH-induced cytoplasmic damage in rat livers according to histopathological observation. Compared to the control group, overproduction of ROS and MDA were observed in rat striatums in the METH alone-treated group, while the lactulose pretreatment significantly attenuated the METH-induced up-regulation of oxidative stress. The lactulose pretreatment significantly repressed over-expressions of proteins of TLR4, MyD88, TRAF6, NFκB, IL-1β, IL-6, TNF-α, cleaved caspase 3, PARP-1. The lactulose pretreatment increased mRNA expressions of Nrf2, p62 and HO-1. These findings suggest that lactulose pretreatment can alleviate METH-induced neurotoxicity through suppressing neuroinflammation and oxidative stress, which might be attributed to the activation of the Nrf2/HO-1 axis.